Zoogeography of Intertidal Communities in the West Indian Ocean as Determined by Ocean Circulation Systems: Patterns from the Tetraclita Barnacles - Tsang, Ling Ming (Public Library of Science, 2012)
The Indian Ocean is the least known ocean in the world with the biogeography of marine species in the West Indian Ocean (WIO) understudied. The hydrography of WIO is characterized by four distinct oceanographic systems and there were few glacial refugia formations in the WIO during the Pleistocene. We used the widely distributed intertidal barnacle Tetraclita to test the hypothesis that the distribution and connectivity of intertidal animals in the WIO are determined by the major oceanographic regime but less influenced by historical events such as Pleistocene glaciations. Tetraclita were studied from 32 locations in the WIO. The diversity and distribution of Tetraclita species in the Indian Ocean were examined based on morphological examination and sequence divergence of two mitochondrial genes (12S rDNA and COI) and one nuclear gene (histone 3, H3). Divergence in DNA sequences revealed the presence of seven evolutionarily significant units (ESUs) of Tetraclita in WIO, with most of them recognized as valid species. The distribution of these ESUs is closely tied to the major oceanographic circulation systems. T. rufotincta is distributed in the Monsoonal Gyre. T. ehsani is present in the Gulf of Oman and NW India. Tetraclita sp. nov. is associated with the Hydrochemical Front at 10°S latitude. T. reni is confined to southern Madagascan and Mauritian waters, influenced by the West Wind Drift. The endemic T. achituvi is restricted to the Red Sea. Tetraclita serrata consists of two ESUs (based on mtDNA analysis) along the east to west coast of South Africa. The two ESUs could not be distinguished from morphological analysis and nuclear H3 sequences. Our results support that intertidal species in the West Indian Ocean are associated with each of the major oceanographic circulation systems which determine gene flow. Geographical distribution is, however, less influenced by the geological history of the region.